2006
DOI: 10.1093/nar/gkl581
|View full text |Cite
|
Sign up to set email alerts
|

CK2-mediated stimulation of Pol I transcription by stabilization of UBF–SL1 interaction

Abstract: High levels of rRNA synthesis by RNA polymerase I are important for cell growth and proliferation. In vitro studies have indicated that the formation of a stable complex between the HMG box factor [Upstream binding factor (UBF)] and SL1 at the rRNA gene promoter is necessary to direct multiple rounds of Pol I transcription initiation. The recruitment of SL1 to the promoter occurs through protein interactions with UBF and is regulated by phosphorylation of UBF. Here we show that the protein kinase CK2 co-immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…CK2 resides in the nucleolus, as well as in the nucleus and cytoplasm, regulates a large number of nucleolar proteins (25) and plays a major role in nucleolar compartmentalization (26). CK2 also regulates the transcriptional activities of all three RNA polymerases (25,(27)(28)(29). In the case of Pol I, CK2 has been found in the rRNA promoter region by ChIP assay and coimmunoprecipitates with the Pol I transcription initiation complex (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…CK2 resides in the nucleolus, as well as in the nucleus and cytoplasm, regulates a large number of nucleolar proteins (25) and plays a major role in nucleolar compartmentalization (26). CK2 also regulates the transcriptional activities of all three RNA polymerases (25,(27)(28)(29). In the case of Pol I, CK2 has been found in the rRNA promoter region by ChIP assay and coimmunoprecipitates with the Pol I transcription initiation complex (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Such a regulatory function is possible for IP5K, which binds CK2, UBF and TCOF1 (Fig. 1F); rRNA synthesis is regulated by interactions between UBF and TCOF1 (Valdez et al, 2004), and also by the phosphorylation of UBF and TCOF1 by CK2 (Isaac et al, 2000;Lin et al, 2006). The facilitation of such communication pathways by IP5K may assist the information flow from cellular signaling cascades, so as to regulate the ribosome production that guides cell differentiation and proliferation (Drygin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…S3). The actions of both UBF and TCOF1 in vivo are modulated by protein kinase CK2 (CK2) (Isaac et al, 2000;Lin et al, 2006). Indeed, CK2 is a key player in the overall regulation of rRNA synthesis so that the degree of ribosomal production can dynamically match changes in cell growth and proliferation (Drygin et al, 2010).…”
Section: Binding Partners For Ip5kmentioning
confidence: 99%
“…Several factors can modulate rRNA synthesis through rDNA transcription, such as the cell growth rate, chromatin structure, rDNA copy number, nutritional status, growth factors and chemical stresses [1][2][3][4][5][6]. Studies in human cells have revealed that selectivity factor 1, which binds to the rDNA gene promoter and promotes recruitment of pol I [7], is regulated by casein kinase 2 (CK2), extracellular signal-regulated kinase and mTOR [8][9][10][11]. CK2 modulates the interaction between selectivity factor 1 and upstream binding factor through upstream binding factor phosphorylation [9,12,13], and rRNA synthesis is promoted by AKT in association with c-Myc and mTORC1 in human cancer-derived cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human cells have revealed that selectivity factor 1, which binds to the rDNA gene promoter and promotes recruitment of pol I [7], is regulated by casein kinase 2 (CK2), extracellular signal-regulated kinase and mTOR [8][9][10][11]. CK2 modulates the interaction between selectivity factor 1 and upstream binding factor through upstream binding factor phosphorylation [9,12,13], and rRNA synthesis is promoted by AKT in association with c-Myc and mTORC1 in human cancer-derived cells [14]. Although the regulation of rDNA transcription has been well characterized, the regulation of RPG transcription is poorly understood.…”
Section: Introductionmentioning
confidence: 99%